Development of Prezi Learning Media Based on Realistic Mathematics Education in Mathematics Learning Materials at SMP Negeri 1 Gunungsitoli Idanoi - Meiman Harapan Zega; Amin Otoni Harefa; Yulisman Zega (CV. Rayyan Dwi Bharata, 2023)
The problems in this study are the lack of students' understanding of the material presented during ongoing learning and the use of instructional media which is limited to blackboards and other relevant sources. The aims of this study were: to know the validity, to know the practicality, to know the effectiveness of RME-based prezi learning media in class VIII SMP Cartesian coordinate material in the learning process. This research is a development research using the ADDIE development model which consists of analysis, design, development, implementation, and evaluation stages. The instrument used is a validation questionnaire which includes aspects of content feasibility, presentation feasibility, and design feasibility, student response questionnaires, and assessment of the practicality of learning media. Research result; (1) media content validity achieved an average rating of 4.94 with very valid criteria, language validity achieved an average result of 4.75 with very valid criteria, and design validity achieved an average value of 4.79 with very valid criteria. (2) the practicality of prezi learning media based on individual tests reaches a percentage of 91% with very practical criteria, small group tests reach a percentage of 87.11% with very practical criteria, field tests reach a percentage of 91.06% with very practical criteria, (3) the effectiveness of prezi learning media achieving an average student score of 81 with very effective criteria.